Prevalence of MB2 canals in maxillary molars using different assessment methods: ex vivo analysis (Research, Society and Development, 2022)
The anatomical complexity of the root canal system of the maxillary molars is considered a challenge to endodontic treatment. The aim of this study was to compare different diagnostic methods for identification of MB2: clinical examination (CE), dental operating microscope (DOM), digital periapical radiography (DR), cone-beam computed tomography (CBCT) and cross sections (CS). Sixty-one maxillary molars were randomly selected. Initially axial images were performed using CBCT. DR were made in ortho-positions, mesial positions and distal positions. The images were evaluated by an experienced examiner, the data were tabulated and not being revealed until the end of the experiment. After those openings and conventional coronary access was made, and the teeth evaluated by CE. Then the teeth were evaluated by DOM. The variable studied presents nominal and dichotomous nature ("absence of MB2 canal" and "presence of MB2 canal"). The agreement between the methods, when compared by pairs, was calculated by Cohen’s Kappa. A major percentual of MB2 detection was obtained by CBCT (67%), follow by CS (55%) and DOM (45%). The concordance between CS and CBCT was substantial (Kappa=0.76; 95%CI: 0.59 to 0.92); between CBCT and DOM was fair (Kappa=0.32; 95%CI: 0.09 to 0.56), as well as between DOM and CE. All the other concordance analysis showed slight agreement (Kappa from 0.00 to 0.20). The identification of MB2 can be facilitated using CBCT and DOM.